1993
DOI: 10.1115/1.2910642
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection Between Two Horizontal Cylinders in an Adiabatic Circular Enclosure

Abstract: A numerical study of natural convection flow structure and heat transfer has been undertaken for air around two horizontal, differentially heated cylinders confined to an adiabatic circular enclosure. Parametric simulations were performed to assess the effects of gap width between cylinders as well as the inclination angle of the enclosure with respect to gravity. Results clearly indicate that the fluid flow complexity and heat transfer characteristics of air amid the cylinders and enclosure wall are strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…Natural convection fluid flow and heat transfer in enclosed spaces with a heater and/or cooler inside are encountered in a number of industrial applications such as indoor ventilation with radiators, cooling of electrical components, and heat exchangers [1]. From energy saving point of view, improvement of heat transfer in any application of natural convection is a primary and crucial topic.…”
Section: Introductionmentioning
confidence: 99%
“…Natural convection fluid flow and heat transfer in enclosed spaces with a heater and/or cooler inside are encountered in a number of industrial applications such as indoor ventilation with radiators, cooling of electrical components, and heat exchangers [1]. From energy saving point of view, improvement of heat transfer in any application of natural convection is a primary and crucial topic.…”
Section: Introductionmentioning
confidence: 99%
“…As a supplement study of Ho's work [17], we conducted a numerical simulation with a relative large ratio of the enclosure diameter to the tube diameter (D/d ¼ 20), in a Rayleigh number range of Ra < 1400, and at various tube orientation angles by using recently prevalent lattice Boltzmann method (LBM). The main purpose of this paper focuses on the natural convection heat transfer between the hot and cold microtubes.…”
Section: Introductionmentioning
confidence: 99%
“…A hot tube arranged in parallel to prevent freezing of liquid or condensing of steam in a cold tube was studied by Kohli [16]. A numerical study and flow visualization for the natural convection between two cylinders with different surface temperatures in an adiabatic circular enclosure were conducted by Ho et al [17], the results indicated that the heat transfer rate is strongly affected by the distance between the two cylinders, the inclination angle between the direction of tube arrangement and gravity in addition to the intensity parameter of Rayleigh number. A wide range of parametric simulations and experimental tests are needed for the internal natural convection with complicated boundary structure.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the vertical con®guration convected less heat than the horizontal one. A numerical study of free convection of air around two horizontal, dierentially heated cylinders con®ned to an adiabatic circular enclosure was reported by Ho et al [4]. They concluded a strong dependency of the¯uid¯ow structure and heat transfer characteristics on the Rayleigh number, the inclination angle and the gap between the cylinders.…”
Section: Introductionmentioning
confidence: 99%